FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMILIHAN ALAT KONTRASEPSI PADA PASANGAN USIA SUBUR (PUS) DI WILAYAH KERJA PUSKESMAS BASUKI RAHMAT KOTA BENGKULU - Metha Fahriani; Buyung Keraman; Yosena Septiana (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2017)
Fertile couples ranged between the ages of 20-45 years where couples are mature enough in everything, especially the reproductive organs are functioning properly. This study aimed to find out the correlation of educational factors, knowledge and socioeconomic status with the selection of contraceptives on fertile couples (PUS) in working area of Basuki Rahmat Public Health Center Bengkulu. Type of research used descriptive correlational with Cross Sectional design using primary data spreading questionnaire with population of 200 PUS with number of sample 134 PUS. Sampling was done by Accidental Sampling. Analysis techniqueswere univariate and bivariate analysis using statistical test that was by